Pretreatment lymphocyte–monocyte ratio as a potential prognostic factor in a cohort of patients with upper tract urothelial carcinoma. Issue 5 (6th February 2015) - Hutterer, Georg C; Sobolev, N; Ehrlich, Georg C; Gutschi, Thomas; Stojakovic, Tatjana; Mannweiler, Sebastian; Pummer, Karl; Zigeuner, Richard; Pichler, Martin; Dalpiaz, Orietta
Abstract : Aims: To investigate the potential prognostic impact of the lymphocyte–monocyte ratio (LMR) in a large European cohort of patients with localised upper urinary tract urothelial carcinoma (UTUC). The LMR as an indicator of systemic inflammatory response has been shown to represent a potential prognostic factor in various types of human cancers. Up to date, the prognostic significance of the LMR in UTUC has not been evaluated. Methods: Clinico-pathological data from 182 non-metastatic patients with UTUC, operated between 1990 and 2012 at a single tertiary academic centre, were evaluated retrospectively. Pretreatment LMR was assessed 1 day before surgery. Patients were categorised using an LMR cut-off value of 2.0 according to a calculation by receiver-operating curve analysis. Patients' overall survival (OS) was assessed using the Kaplan–Meier method. To evaluate the independent prognostic significance of the LMR, a multivariate proportional Cox regression model was applied for OS. Results: In multivariate analyses, age on the date of surgery (<65 vs ≥65 years, HR=2.10, 95% CI 1.22 to 3.64), pathological T-stage (pT1 vs pT2–4, HR=2.15, 95% CI 1.26 to 3.67), as well as the LMR (<2 vs ≥2, HR=0.56, 95% CI 0.35 to 0.92) were independent predictors of OS of patients with UTUC. Conclusions: In the cohort studied, patients with an elevated (≥2) preoperative LMR had a subsequently longer OS after radical surgery for UTUC, compared with those with a low (<2) preoperative LMR. Thus, we believe this parameter might be considered an additional prognostic factor in UTUC in the future.